Innovative and Affordable Feed Solutions for Enhancing Cattle Finishing in Tanzania (Global Journal of Science Frontier Research, 2024)
In Tanzania livestock is important in building the national economy and is considered the first and second livelihood driver The beef sub-sector contributes about 2 2 of the GDP compared to other livestock species and products However most cattle are brought to the slaughterhouses while unfinished Proper finishing is crucial because it adds value to the quality of beef meat Apart from genetics applying the right feed technology and feeding strategies on beef cattle before slaughter can increase output by 70 and perhaps coequal with health The current study developed two feed diet formulas using local feed materials giventhe high quality and affordable costfor the Zebu cattle finishing business A total of 60 mainly Tanzanian Short Horn Zebu SHZ cattle 24 females and 36 males with three age categories less than 3 3-4 more than 4 years were randomly assigned to individual feeding pensand three treatments two formulated diets and one control for 11 weeks and only 8 weeks Week 3 to Week 10 of the experiment data were considered in the analysis for the current paper and other experimental protocols were observed Also the experiment has Phase I and Phase II for validation The diet comprised Maize meal Cassava root meal and Rice Polish as energy sources while Leucaena Leaf meal Soya bean meal and Sunflower seed cake were protein sources in both diet formulas with varying energy amounts
Keywords: cattle; finishing; fattening; feed formula; diet